2020
DOI: 10.3389/fpls.2020.00325
|View full text |Cite
|
Sign up to set email alerts
|

The Geomagnetic Field Is a Contributing Factor for an Efficient Iron Uptake in Arabidopsis thaliana

Abstract: The Earth's magnetic field, defined as the geomagnetic field (GMF), is an unavoidable environmental factor for all living organisms. Variation in the GMF intensity was found to affect the content of some nutrients and their associated channels and transporters in Arabidopsis thaliana. In this work, we observed that reduction of the GMF to near null magnetic field (NNMF) affects the accumulation of metals in plant tissues, mainly iron (Fe) and zinc (Zn) content, while the content of others metals such as copper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 52 publications
(68 reference statements)
2
24
0
1
Order By: Relevance
“…First and second youngest N. tabacum leaves (of at least 8 cm in length) and stems were sampled from 10 weeks old plants, whereas their seeds were collected from ripened seed capsules. Leaves, stems and seeds were dried at 100°C, mineralized and the concentrations of various elements were measured by inductively coupled plasma mass spectrometry (ICP-MS) as in (Islam et al 2020); the statistical analyses were performed according to (Martin-Sanchez et al 2020).…”
Section: Element Analyses In N Tabacummentioning
confidence: 99%
“…First and second youngest N. tabacum leaves (of at least 8 cm in length) and stems were sampled from 10 weeks old plants, whereas their seeds were collected from ripened seed capsules. Leaves, stems and seeds were dried at 100°C, mineralized and the concentrations of various elements were measured by inductively coupled plasma mass spectrometry (ICP-MS) as in (Islam et al 2020); the statistical analyses were performed according to (Martin-Sanchez et al 2020).…”
Section: Element Analyses In N Tabacummentioning
confidence: 99%
“…Among the natural components of our planet, such as water, temperature, climate and electric charges, Earth's magnetic field or geomagnetic field (GMF) is a component that influences many biological processes in plants [15][16][17][18]. As a sessile organism, plants show different levels of morphophysiological and molecular responses under different magnetic field (MF) intensities, such as shoot, root and stem elongation, photosynthetic performance, plant nutrient uptake and the expression of several genes associated with photoreceptors [8,[18][19][20]. Accordingly, many researchers have used a static magnetic field (SMF) to influence plant growth and development and to reduce cellular oxidative stress under unfavorable environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…It eventually also affected the plant's growth and development immediately after exposure to the reduced MF (Narayana et al, 2018 ). The accumulation of metals in plant tissues, mainly iron and zinc content, were affected under near null magnetic field (NNMF) condition and iron uptake genes were induced in the roots of NNMF-exposed plants (Islam et al, 2020 ). Under iron deficiency, NNMF-exposed plants displayed a limitation in the activation of iron-deficiency-induced genes, leading to the substantial accumulation of zinc and copper.…”
Section: Discussionmentioning
confidence: 99%
“…Under iron deficiency, NNMF-exposed plants displayed a limitation in the activation of iron-deficiency-induced genes, leading to the substantial accumulation of zinc and copper. Further, it was concluded that GMF could contribute to efficient iron uptake in Arabidopsis thaliana (Islam et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%